Seeded optical parametric generation in CdSiP2 pumped by a nanosecond pulsed, MHz repetition rate Raman fiber amplifier at 1.24 µm - Murray,RT; Chandran,AM; Battle,RA; Runcorn,TH; Schunemann,PG; Zawilski,KT; Guha,S; Taylor,JR (SPIE, 2021)
We report a CdSiP2 (CSP) based seeded optical parametric generator (OPG), emitting sub-nanosecond duration, 3 MHz repetition rate, wavelength tunable mid-infrared (MIR) light at 4.2-4.6 μm. We generate up to 0.25 W at 4.2 μm with a total pump conversion efficiency of 42%. The OPG is pumped by a 1.24 μm Raman fiber amplifier system. This is the first demonstration of pumping CSP with a Raman fiber source in this region, and we show that Raman fiber sources in the near-infrared (NIR) are ideal pump sources for non-critically phasematched (NCPM) CSP devices. Pumping CSP at 1.24 μm permits the use of NCPM whilst decreasing the negative effects of both two-photon absorption and linear absorption losses, when compared to conventional 1 μm pumping. This offers a potential advantage for MIR power scaling of CSP parametric devices due to a reduced thermal load in the crystal from residual pump absorption. The OPG is seeded with a continuous-wave fiber supercontinuum source emitting radiation in the 1.7 μm region, to lower the threshold pump intensity required for efficient conversion. NCPM and temperature tuning of the crystal allow for simple wavelength tuning of the idler radiation. We report on laser damage induced by elevated crystal temperatures, which we propose is linked to the decrease in CSP bandgap energy with increasing temperature.